Homogeneous catalytic oxidation of styrene and styrene derivatives with hydrogen peroxide in the presence of transition metal-substituted polyoxotungstates - Duarte, Tiago A. G.
The tetrabutylammonium (TBA) salts of the Keggin-type polyoxotungstates with general formula [XW11M(H2O)O-39]((n-m)-), where X = P, B or Si and M = Mn, Fe or Co, were evaluated as catalysts in the oxidation of styrene, alpha-methylstyrene, p-methylstyrene, alpha,p-dimethylstyrene, p-chlorostyrene, p-nitrostyrene, and p-methoxystyrene under mild conditions, using aqueous H2O2 as an eco-sustainable oxidant. In this study, the influence of the catalysts and of the different styrene substituents on the oxidation reaction profile was evaluated in terms of conversion and selectivity. For all the performed catalytic studies, the main product results from the oxidative cleavage of the vinyl double bond, except in the case of the oxidation of p-methoxystyrene catalysed by BW11Mn, for which p-methoxyphenol is the main product. The catalysts BW11Mn and SiW11Co give rise to 100% conversion for almost all of the substrates, excluding p-methoxystyrene and p-nitrostyrene for both catalysts and alpha,p-dimethylstyrene only in the case of BW11Mn. The selectivity for C=C cleavage products resulting from the oxidative cleavage of the vinyl double bond can be as high as 98%, reaching 98% conversion for p-nitrostyrene when SiW11Co was used as a catalyst. Possible pathways are discussed and the oxidation of a few presumed intermediates was carried out. The systematic study of several substituted styrene derivatives suggests a possible reactivity order for these compounds in the catalytic system considered.